The Influence Of Tiktok Affiliate Content Marketing And Online Customer Reviews On Tiktok E-Commerce Users' Purchase Intention - Alfarizi, Aldi; Wijaya , Ermy; Febliasa , Muhammad Rahman (Utami Publisher, 2025)
This study aims to determine the influence of TikTok Affiliate Content Marketing and Online Customer Reviews on purchase intention among students in Bengkulu who use TikTok E-commerce. This associative quantitative study involves 150 respondents selected through purposive sampling. Data was collected using a Likert scale questionnaire and analyzed using multiple linear regression via SPSS version 25. The findings show that both Content Marketing (X₁) and Online Customer Reviews (X₂) significantly affect Purchase Intention (Y) both partially and simultaneously. This is indicated by t-values of 6.109 and 9.103 respectively, exceeding the t-table value of 1.976, and an F-value of 222.368 > 3.91 at a significance level of 0.000. The coefficient of determination (R²) is 0.752, meaning 75.2% of purchase intention variation is explained by these two variables. This suggests that stronger content marketing and positive online reviews significantly enhance consumers’ purchase intentions on TikTok Shop.